Joan Mitchell interviewed by Sue Mitchell for the Australia 1938 oral history project - Mitchell, Joan, 1919-; Mitchell, Sue; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1981)
Mitchell speaks of her home and living conditions; family life and lifestyle; entertainment and recreation; health care; schooling and childhood memories; employment experiences and conditions; social life; memories of the 1930s.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Timed summary available.
Keywords: Mitchell, Joan, -- 1919- -- Interviews; Newcastle (N.S.W.) -- Social conditions; Australia -- Social conditions -- 1901-1945.; Australia -- Social life and customs -- 1901-1945.; Australia -- History -- 1901-1945.